2012
DOI: 10.1063/1.4752269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain boundary on the electromechanical response of ferroelectric polycrystals

Abstract: The effect of grain boundaries on the electromechanical response of a ferroelectric polycrystal subjected to an electric field or stress is investigated numerically by using a phase field model. The grain boundaries in the phase field model are regarded as dielectrics in which the ferroelectric properties are degraded completely. The phase field simulations show that the presence of dielectric grain boundaries results in a large build-in depolarizing field in grains. The depolarizing field has a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…In the phase-field model of ferroelectric materials, the polarization vector P = (P 1 , P 2 , P 3 ) is taken as the order parameter to describe the free energies of ferroelectric systems. The total free energy of the ferroelectric system F, can be described by [62]:…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phase-field model of ferroelectric materials, the polarization vector P = (P 1 , P 2 , P 3 ) is taken as the order parameter to describe the free energies of ferroelectric systems. The total free energy of the ferroelectric system F, can be described by [62]:…”
Section: Computational Detailsmentioning
confidence: 99%
“…dF/dP i (r,t) represents the thermodynamic driving force for the spatial and temporal evolution of the ferroelectric system. Using the variation or principle of virtual work, the weak form (or integral form) of the governing equation can be obtained as [51,62]:…”
Section: Computational Detailsmentioning
confidence: 99%
“…And the full affection of domain boundary is still to be discovered. Similar but more significant grain boundaries are simulated by Tong-Yi Zhang's group [16], in a real space phase field model, they define that grain boundary to be of finite width and with same mechanical property but dielectric. It is found that the existence of finite width grain boundary introduce a large depolarization energy, increased piezoelectric coefficient and permittivity of polycrystalline ferroelectrics.…”
Section: Simulation For Ferroelectric Materialsmentioning
confidence: 99%
“…It is found that the existence of finite width grain boundary introduce a large depolarization energy, increased piezoelectric coefficient and permittivity of polycrystalline ferroelectrics. And the increase of grain boundary thickness is related to decreasing of coercive field form the hysteresis loop [16].…”
Section: Simulation For Ferroelectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation